Influence of fault current on electromagnetic-thermal characteristics of HTS coated conductors. (January 2023) - Chen, Wei; Jin, Rong; Wang, Shuxin; Ye, Yunyang; Che, Tong; Liu, Liyuan; Shen, Boyang; Yang, Xinsheng; Zhao, Yong
Highlights: At a high fault current, the transport current in the tape will be shunted. The losses of the two kinds of structural tape under different fault currents show obvious differences. The temperature rise of type B tape is smaller at same fault current, and it has a relatively better fault tolerance. Abstract: In this paper, the electromagnetic-thermal coupling numerical model is used to study the loss and temperature distribution of two typical high temperature superconducting (HTS) coated conductors (CCs) under short-circuit fault, as well as the dynamic evolution law with time. The electromagnetic module adopts the widely used H -formulation, and the thermal module adopts the general form of heat conduction equation. The coupling between the two module is realized by using the loss calculated by the electromagnetic module as the heat source of the thermal module and combining the J c0 ( B, T ) relationship. A modified E - J relation suitable for any current density range is used to describe the resistivity of superconductors. Due to the difference of magnetic and thermal properties of the two kinds of structural tape substrate materials and geometric dimensions of copper stabilized layer, the losses of the two kinds of structural tape under different fault currents show obvious differences. At low fault transport current, the magnetic substrate of type B tape (NiW substrate) will obviously make the magnetic flux density perpendicular to the superconducting layer greater than that of type A tape (Hastelloy substrate), thus making the loss of type B tape greater. Under the condition of high fault transport current, the fault current will be shunted between different layers of the tape. Type B tape has a thicker copper stabilizer, which makes the current density of type B tape copper layer lower than that of type A tape, and the temperature rise and loss of type B tape are lower. Specifically, when I p / I c0 is less than about 0.65, the total loss of type A tape is less than that of type B tape. When I p / I c0 is greater than about 0.65, the total loss of type A tape is greater than that of type B tape.